Azithromycin with scaling and root planing versus scaling and root planing alone in the treatment of periodontitis: A randomized controlled trial - Viktoriya I. Shynkevych; Svitlana V. Kolomiiets; Igor P. Kaidashev (Elsevier, 2023)
Background: The growing interest in the possibilities of macrophages modulation with therapeutic purposes promotes new approaches for periodontitis treatment. Aim: The aim of this randomized controlled open clinical study was to evaluate the early clinical and immunological effects of the long-course azithromycin as an adjunct to scaling and root planing in periodontitis. Methods: 50 patients (with stage I-III, grade A/B periodontitis) and 22 periodontally healthy volunteers as the reference group were recruited. Following scaling and root planing (SRP), the patients were randomly assigned to one of two treatment modalities: SRP only (n = 25) and adjunct azithromycin (Az) treatment (n = 25). The patients were monitored at baseline, and 30 ± 5 days after therapy. Clinical attachment loss (CAL), periodontal probing depth (PPD) and bleeding on probing (BoP) were evaluated. Secondary outcome measures included mean changes in single-positive CD68 + and CD163 + macrophages (Mφs) density and ratio, evaluated by immunohistochemistry, and IL1-β, IL-6, IL-10, TGF-β levels, detected by ELISA. Results: At 1 month both groups showed significant improvements of CAL, PPD and BoP, without significant added benefit in terms of CAL, PPD and BoP of Az. But Az increased the density of CD68 + and CD163 + Mφs (P < 0.0001), decreased the CD68+/CD163 + ratio (P = 0.043), decreased IL-1β (P < 0.01), IL-6 (P < 0.001) levels, and increased IL-10 (P < 0.0001) and TGF-β (P < 0.001) levels compared to SRP and periodontitis at baseline. Conclusion: The long course of Az demonstrated modulation of CD68 + and CD163 + Mφs towards M2 polarization, which may play a significant role in achieving favorable long-term treatment outcomes. ClinicalTrials.gov